Does three months genistein and daidzein in the form of soy protein supplementation have any effects on bone formation markers after menopause? - Haghighian Roudsari, Arezoo; Kimiagar, Masoud; Larijani, Bagher; Zamanian Azodi, Mona (Archives of Advances in Biosciences, 2013)
Postmenopausal osteoporosis is caused by a sharp decrease in estrogen levels leading to an increased rate of bone remodeling. Dietary supplements are preferred as alternative therapeutic options for many women instead of estrogen therapy. These alternative therapies include the use of natural substances such as soy isoflavones due to their weak estrogenic activity and affinity for estrogen receptors.Present study was carried out as a "before and after clinical trial" on 25 postmenopausal women aged 45-64 years. Soy protein at 35g level containing 98.3mg isoflavones (containing 47.2 genistein and 37.8 daidzein) were given to subjects daily for 12 weeks. Blood and urine samplings were done in 3 stages, in the beginning and at the end of 6th and 12th week. Repeated measurement analysis was employed to analyze any possible changes in food intake and biochemical variables in 3 stages. The level of significance was set at below 5 percent (P<0.05). Mean body mass index and physical activity level had no change and mean daily intake of macronutrients and important micronutrients were not different at 6 and 12 weeks compared to the start of the study The results showed a total serum alkaline phosphatase (TALP) significant increase while the other bone formation indicators namely osteocalcin and insulin growth factor binding protein (IGFBP3) did not change significantly. These data suggest that soy protein or its isoflavones may increase bone formation by supplementation.